Superior tensile properties in additively manufactured Ti alloys. Issue 5 (20th October 2021) - Zafari, A.; Chandran, P.; Xia, K.
ABSTRACT: Thanks to rapid cooling rates and small melt pool sizes, selective laser melting (SLM) can be used to create novel microstructures difficult or impossible to achieve otherwise. This article overviews two types of SLM-fabricated Ti alloys exhibiting excellent strength and ductility. First, fully martensitic Ti-6Al-4 V alloys are produced with high yield strengths of >1100 MPa and total elongations of 12–14%, comparable to those in fine α/β lamellar Ti-6Al-4 V. Second, hybridisation of different microstructures from existing alloys to generate a 'composite of microstructures' is introduced as a new strategy for producing heterogenous alloys with significantly enhanced performances. In particular, Ti alloys hybridised from different classes of Ti (α, α-β and β) have exhibited an excellent combination of high strength, work hardening ability and ductility, superior to conventional pure Ti andTi alloys.